Sustainability Performance Differences of Industrial Heritage Regeneration Implementation Modes - Tong Chu; Minghao Zhou; Jiang Wu (Buildings)
In high-density cities around the world, the contradiction of sustaining development and limited resources has become more evident. Transforming historic industrial buildings, through both functional and spatial adjustments, has emerged as a key strategy to manage these challenges effectively. There is a significant demand for the quick regeneration of industrial heritage districts, resulting in the emergence of various implementation modes (IMs). While the Sustainable Development Goals (SDGs) have gained widespread acceptance, the integration of sustainability principles into urban regeneration practices has strengthened globally. However, in many regions, approaches to achieving sustainable regeneration are still unclear, with a lack of evaluation and adjustment of sustainability performance (SP). This paper combines qualitative analysis and a quantitative assessment of indicators to compare three representative case studies with different IMs. It explores whether there is a connection between the chosen IM and SP, examines the mechanisms of impact, and discusses how to select the most suitable IM for industrial heritage regeneration. The study confirms the practicality of an SP evaluation system and identifies key factors within IMs that affect SP. Future research is expected to produce tools that support the promotion of sustainability in industrial heritage regeneration efforts.